2022
DOI: 10.1155/2022/3517995
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Design of Service Robot Based on User Emotion Recognition and Environmental Monitoring

Abstract: Robots may be able to comprehend human emotions better by adding speech emotion recognition and environment monitoring functions to human-computer interaction systems. Robots can offer more humanized services by adapting to human emotions, resulting in a comfortable and cordial interaction between humans and robots. Improve the environment for communication and computer-human interaction and also interactive computer experience. In order for service robots to perform fluid human-computer interaction, this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Service robots in the health care sector can aid patients with cognitive obstruction via built-in affective computing algorithms [ 58 ]. In commerce, empowering service robots with emotion recognition is a highly popular topic in research [ 59 , 60 , 61 , 62 , 63 , 64 ]. Some emotion recognition databases are available for service robots [ 65 , 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…Service robots in the health care sector can aid patients with cognitive obstruction via built-in affective computing algorithms [ 58 ]. In commerce, empowering service robots with emotion recognition is a highly popular topic in research [ 59 , 60 , 61 , 62 , 63 , 64 ]. Some emotion recognition databases are available for service robots [ 65 , 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%